2011
DOI: 10.1016/j.compag.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Automatic grading of Bi-colored apples by multispectral machine vision

Abstract: In this paper we present a novel application work for grading of apple fruits by machine vision. Following precise segmentation of defects by minimal confusion with stem/calyx areas on multispectral images, statistical, textural and geometric features are extracted from the segmented area. Using these features, statistical and syntactical classifiers are trained for two-and multi-category grading of the fruits. Results showed that feature selection provided improved performance by retaining only the important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(50 citation statements)
references
References 32 publications
0
46
0
4
Order By: Relevance
“…The major focus and intension of the technique is to use existing data to invent new facts and to uncover new relationships previously unknown even to the experts [21]. In Agriculture, Data Mining techniques have been recently used for recognizing and grading fruits [22]. In China, the relation between climate change, water resources and agriculture was undertaken using the technique of Data Mining [23].…”
Section: Ability To Learnmentioning
confidence: 99%
“…The major focus and intension of the technique is to use existing data to invent new facts and to uncover new relationships previously unknown even to the experts [21]. In Agriculture, Data Mining techniques have been recently used for recognizing and grading fruits [22]. In China, the relation between climate change, water resources and agriculture was undertaken using the technique of Data Mining [23].…”
Section: Ability To Learnmentioning
confidence: 99%
“…Several recent research studies have been carried out to develop image-processing methods for the detection of defective apples (Bhatt et al, 2012;Garrido-Novell et al, 2012;Kim et al, 2007;Srivastava, 2012;Unay et al, 2011). Using processing and analysis methods for full-target images, these studies found that effective algorithms could be developed for non-destructive detection of defective apples using a variety of machine vision systems.…”
Section: Introductionmentioning
confidence: 99%
“…Once the color space is specified, color feature can be extracted from images or regions. A number of important color features have been proposed in the literatures, including color histogram [13], color moments(CM) , color coherence vector (CCV) and color correlogram , etc [22]. Texture is one of the important features of an image.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Jonagold, Fuji). Inspection of the latter group by image processing is more problematic because of color transition areas [13]. According to a plant pathology factsheet, common diseases found in apple are: Apple Scab, Apple Rot, Apple Blotch and Cork Spots.…”
Section: Introductionmentioning
confidence: 99%